Strategi Bertahan Hidup Masyarakat Korban Lumpur Lapindo Di Perumahan Renojoyo Desa Kedung Kampil Kecamatan Porong Kabupaten Sidoarjo - Sefia Esa Puspita Anggraeni; Vinda Olivia Hanna; Virna Muhdelifa Desembrianti (Universitas Katolik Widya Karya Malang, 2023)
Sidoarjo Regency has a beach in the eastern region along 27 km which crosses several sub-districts such as Sedati, Buduran, Sidoarjo, Porong and Jabon. The Lapindo mud disaster that occurred in 2006 in Sidoarjo had a broad impact on people's daily lives. The Lapindo mud disaster was an event of hot mudflow and the emergence of gas onto the ground which claimed many lives and had a major direct impact on the community. The occurrence of the Lapindo mud disaster was initiated by oil drilling from PT. Lapindo Brantas Inc., which was later in the drilling process, experienced a failure resulting in an explosion from underground and then gushing out. Many were victims in the incident ranging from babies, children, adults to the elderly and many people, houses, villages, districts, schools and other buildings were drowned. In addition, many people have lost their jobs and their homes which makes them all feel stressed to the point of depression. Until now, the problems caused by the Lapindo mudflow disaster have not been resolved. This is because the responsibility for compensation that is given is not evenly distributed or does not even receive a penny. As a result, there are still frequent conflicts and prolonged demonstrations. Meanwhile, the victims of the Lapindo mudflow have used many strategies to survive and continue their lives so that they do not continue to mourn the sadness that exists.